Geophysical Analysis in Kaliulo Warm Water, Central Java - yunita, lia; Neni C.P, Anastasia (ReTII, 2020)
Warm water in Kaliulo Semarang is one of the manifestations of geothermal energy in the Ungaran-Telomoyo-Merbabu-Merapi volcanic area which has the potential for geothermal utilization. The temperature of Kaliulo hot water is around 36-48 0C. This study aims to perform a geophysical analysis around the Kaliulo hot springs to prove the presence of magnetic and anomalies. The methodology used using the magnetic method is correlated with geological data which includes stratigraphic and topographic maps. The equipment used includes the Proton Precision Magnetometer Ground Positioning System, laptop and surfer 15 software and Oasis version 7.0.1 for data processing. up to 1.3 nT through IGRF and daily corrections, this proves that there are magnetic anomalies around warm water manifestations and based on the stacking map there is a continuous structure with increasing depth. The lowest magnetic anomaly values ​​were found around the Kaliulo warm water manifestations.